Use of fumaric acid to control pH and inhibit malolactic fermentation in wines - Morata, Antonio (2019)
ABSTRACT Fumaric acid is an additive allowed by the Codex Alimentarius and under evaluation by the International Organisation of Vine and Wine (OIV) that can be used for wine acidification but also to inhibit malolactic fermentation (MLF). The use of 300–900 mg/L of fumaric acid can inhibit MLF in red wines decreasing pH by 0.2 units or more depending on the buffer capacity. When MLF was running with populations of either 7 or 8 log CFU/mL strain alpha (Oenococcus oeni) the application of 600 mg/L of fumaric acid stopped the process for more than 50 days and cells were undetected in specific media. In triangular tastings, fumaric acid was not detected at 300–600 mg/L (p < .05). In subsequent preference tests, some tasters perceived more acidity and body. Fumaric acid is a useful technological additive to improve wine microbiological stability and freshness, also allowing reduction of SO2 levels.